A retrospective study (2006–2020) of biopsy cases in pet guinea pigs (Cavia porcellus), degus (Octodon degus) and chinchillas (Chinchilla lanigera) at an exotic animal clinic in Tokyo, Japan - Minato Ueda; Takanori Shiga; Yasutsugu Miwa; Makoto Nakata; James K. Chambers; Kazuyuki Uchida; Nobuo Sasaki; Hiroyuki Nakayama (Journal of Comparative Pathology, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Effects of amount of lactose in milk replacer on gastrointestinal function of dairy calves - R. Fukumori; T. Nakayama; M. Hirose; I. Norimura; K. Izumi; K. Shimada; H. Mineo; M.A. Steele; S. Gondaira; H. Higuchi; T. Watanabe; H. Ueda; et al. (Animal Feed Science and Technology, 2025)

Regression and trend analysis of LEAP 2020 experimental results - Mourad Zeghal; Alejandro Sepulveda; Majid T. Manzari; Bruce Kutter; Tarek Abdoun; Stuart K. Haigh; Wen-Yi Hung; Evangelia Korre; Gopal S.P. Madabhushi; Satish Manandhar; Mitsu Okamura; Kyohei Ueda; et al. (Soil Dynamics and Earthquake Engineering, 2024)

Correlation of CPT measurements and relative density of LEAP-2017 and LEAP-2020 centrifuge models - Alejandro Sepulveda; Mourad Zeghal; Bruce L. Kutter; Majid T. Manzari; Tarek Abdoun; Sandra Escoffier; Stuart K. Haigh; Wen-Yi Hung; Evangelia Korre; Gopal S.P. Madabhushi; Satish Manandhar; Mitsu Okamura; et al. (Soil Dynamics and Earthquake Engineering, 2024)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Perlecan Domain-V Enhances Neurogenic Brain Repair After Stroke in Mice - Amanda L. Trout; Michael P. Kahle; Jill M. Roberts; Aileen Marcelo; Leon de Hoog; Jeffery A. Boychuk; Stephen L. Grupke; Antonio Berretta; Emma K. Gowing; Carie R. Boychuk; Amanda A. Gorman; Danielle N. Edwards; et al. (Translational Stroke Research, 2021)
The extracellular matrix fragment perlecan domain V is neuroprotective and functionally restorative following experimental stroke. As neurogenesis is an important component of chronic post-stroke repair, and previous studies have implicated perlecan in developmental neurogenesis, we hypothesized that domain V could have a broad therapeutic window by enhancing neurogenesis after stroke. We demonstrated that domain V is chronically increased in the brains of human stroke patients, suggesting that it is present during post-stroke neurogenic periods. Furthermore, perlecan deficient mice had significantly less neuroblast precursor cells after experimental stroke. Seven-day delayed domain V administration enhanced neurogenesis and restored peri-infarct excitatory synaptic drive to neocortical layer 2/3 pyramidal neurons after experimental stroke. Domain V’s effects were inhibited by blockade of α2β1 integrin, suggesting the importance of α2β1 integrin to neurogenesis and domain V neurogenic effects. Our results demonstrate that perlecan plays a previously unrecognized role in post-stroke neurogenesis and that delayed DV administration after experimental stroke enhances neurogenesis and improves recovery in an α2β1 integrin-mediated fashion. We conclude that domain V is a clinically relevant neuroprotective and neuroreparative novel stroke therapy with a broad therapeutic window.

Determination of Rate and Extent of Scopolamine Release from Transderm Scōp® Transdermal Drug Delivery Systems in Healthy Human Adults - Suresh Kumar Swaminathan; Caroline Strasinger; Megan Kelchen; Jamie Carr; Wei Ye; Anna Wokovich; Priyanka Ghosh; Srinivasan Rajagopal; Kenichi Ueda; James Fisher; Karunya K. Kandimalla; Nicole K. Brogden (AAPS PharmSciTech, 2020)

Correction to: Common findings of blaCTX-M-55-encoding 104–139 kbp plasmids harbored by extended-spectrum β-lactamase-producing Escherichia coli in pork meat, wholesale market workers, and patients with urinary tract infection in Vietnam - T. A. V. Hoang; T. N. H. Nguyen; S. Ueda; Q. P. Le; T. T. N. Tran; T. N. D. Nguyen; T. V. K. Dao; M. T. Tran; T. T. T. Le; T. L. Le; T. Nakayama; I. Hirai; et al. (Current Microbiology, 2019)

Effects of Transcranial Direct Current Stimulation of the Posterior Parietal Cortex on the Control of Visual Attention - Y. Hirakawa; K. Takeda; S. Tanabe; S. Koyama; T. Ueda; K Morishima; M. Iwai; S. Kuno; I. Motoya; H. Sakurai; Y. Kanada (Neurophysiology, 2019)

The behavioural homing response of adult chum salmon Oncorhynchus keta to amino‐acid profiles - E. Y. Chen; J. B. K. Leonard; H. Ueda (Journal of Fish Biology, 2017)
Adult chum salmon Oncorhynchus keta homing behaviour in a two‐choice test tank (Y‐maze) was monitored using a passive integrated transponder (PIT)‐tag system in response to river‐specific dissolved free amino‐acid ( DFAA ) profiles and revealed that the majority of O. keta showed a preference for artificial natal‐stream water and tended to stay in this maze arm for a longer period; natal‐stream water was chosen over a nearby tributary's water, but not when the O. keta were presented with a non‐tributary water. The results demonstrate the ability of O. keta to discriminate artificial stream waters containing natural levels of DFAA .

Common findings of bla CTX-M-55-encoding 104–139 kbp plasmids harbored by extended-spectrum β-lactamase-producing Escherichia coli in pork meat, wholesale market workers, and patients with urinary tract infection in Vietnam - T. A. V. Hoang; T. N. H. Nguyen; S. Ueda; Q. P. Le; T. T. N. Tran; T. N. D. Nguyen; T. V. K. Dao; M. T. Tran; T. T. T. Le; T. L. Le; T. Nakayama; I. Hirai; et al. (Current Microbiology, 2017)

Enhanced loading regimen of teicoplanin is necessary to achieve therapeutic pharmacokinetics levels for the improvement of clinical outcomes in patients with renal dysfunction - T. Ueda; Y. Takesue; K. Nakajima; K. Ichiki; A. Doita; Y. Wada; T. Tsuchida; Y. Takahashi; M. Ishihara; H. Ikeuchi; M. Uchino; T. Kimura (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Jasmonate signaling is activated in the very early stages of iron deficiency responses in rice roots - Takanori Kobayashi; Reiko Nakanishi Itai; Takeshi Senoura; Takaya Oikawa; Yasuhiro Ishimaru; Minoru Ueda; Hiromi Nakanishi; Naoko K. Nishizawa (Plant Molecular Biology, 2016)

Ecological differences in response of bird species to radioactivity from Chernobyl and Fukushima - A. P. Møller; T. A. Mousseau; I. Nishiumi; K. Ueda (Journal of Ornithology, 2015)

Revision of Begomovirus taxonomy based on pairwise sequence comparisons - Judith K. Brown; F. Murilo Zerbini; Jesús Navas-Castillo; Enrique Moriones; Roberto Ramos-Sobrinho; José C. F. Silva; Elvira Fiallo-Olivé; Rob W. Briddon; Cecilia Hernández-Zepeda; Ali Idris; V. G. Malathi; Darren P. Martin; et al. (Archives of Virology, 2015)

Iron deficiency regulated OsOPT7 is essential for iron homeostasis in rice - Khurram Bashir; Yasuhiro Ishimaru; Reiko Nakanishi Itai; Takeshi Senoura; Michiko Takahashi; Gynheung An; Takaya Oikawa; Minoru Ueda; Aiko Sato; Nobuyuki Uozumi; Hiromi Nakanishi; Naoko K. Nishizawa (Plant Molecular Biology, 2015)

Trks are novel oncogenes involved in the induction of neovascularization, tumor progression, and nodal metastasis in oral squamous cell carcinoma - Tomonori Sasahira; Nobuhiro Ueda; Kazuhiko Yamamoto; Ujjal K. Bhawal; Miyako Kurihara; Tadaaki Kirita; Hiroki Kuniyasu (Clinical & Experimental Metastasis, 2013)

Characterization of a new anulavirus isolated from Amazon lily plants - S. Fuji; M. Kikuchi; S. Ueda; T. Toda; H. Furuya; F. Fukumoto; K. Hanada (Archives of Virology, 2013)

Distribution of prolactin receptors suggests an intraductal role for prolactin in the mouse and human mammary gland, a finding supported by analysis of signaling in polarized monolayer cultures - Eric K. Ueda; KuangTzu Huang; Virginia Nguyen; Marco Ferreira; Saudade Andre; Ameae M. Walker (Cell and Tissue Research, 2011)

Migratory behaviour of adult chum salmon, Oncorhynchus keta , in a reconstructed reach of the Shibetsu River, Japan - Y. MAKIGUCHI; H. NII; K. NAKAO; H. UEDA (Fisheries Management and Ecology, 2008)
During 2004–2006, 30 adult chum salmon, Oncorhynchus keta (Walbaum), were tagged with electromyogram (EMG) transmitters and depth/temperature loggers and tracked along both the channelised and reconstructed segments of the Shibetsu River, Japan to assess the effects of the river re‐meandering construction on upstream migration. Holding time of chum salmon in the reconstructed segment was longer than in the channelised segment. Further, greater diversity of physical condition in water velocity was observed in the reconstructed segment in 2005. Swimming speeds decreased during holding and often exceeded the critical swimming speed ( U crit ). It appears that the physical characteristics developed in the reconstructed segment may be suitable for holding of chum salmon. Further, swimming speed exceeding U crit prior to holding may be exhaustive so holding behaviour may be important for muscle recovery as well as for efficient swimming to reduce the energetic cost during upstream migration.

Unique grouping of the Far East Asian begomovirus complex based on sequence analyses of the DNA-A genome and associated DNAβ satellite molecules isolated from tomato, honeysuckle and Eupatorium plants in Japan - S. Ueda; M. Onuki; K. Hanada; Y. Takanami (Archives of Virology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Upstream migration of adult chum and pink salmon in the Shibetsu River - Y. Makiguchi; H. Nii; K. Nakao; H. Ueda (Hydrobiologia, 2007)

Bovine and water buffalo Mx2 genes: polymorphism and antiviral activity - H. A. E. Babiker; Y. Nakatsu; K. Yamada; A. Yoneda; A. Takada; J. Ueda; H. Hata; T. Watanabe (Immunogenetics, 2006)

First report of the Q biotype ofBemisia tabaci in Japan by mitochondrial cytochrome oxidase I sequence analysis - S. Ueda; J. K. Brown (Phytoparasitica, 2006)

Roles of Aquaporin-3 Water Channels in Volume-Regulatory Water Flow in a Human Epithelial Cell Line - H. Kida; T. Miyoshi; K. Manabe; N. Takahashi; T. Konno; S. Ueda; T. Chiba; T. Shimizu; Y. Okada; S. Morishima (The Journal of Membrane Biology, 2005)

Complete nucleotide sequences of attenuated and severe isolates of Leek yellow stripe virus from garlic in northern Japan: Identification of three distinct virus types in garlic and leek world-wide - F. Takaki; T. Sano; K. Yamashita; T. Fujita; K. Ueda; T. Kato (Archives of Virology, 2005)

Elimination of chrysanthemum stunt viroid from an infected chrysanthemum cultivar by shoot regeneration from a leaf primordium-free shoot apical meristem dome attached to a root tip - M. Hosokawa; A. Otake; K. Ohishi; E. Ueda; T. Hayashi; S. Yazawa (Plant Cell Reports, 2004)

FISH-Mapping of 18S Ribosomal RNA Genes and Telomeric Sequences in the Japanese Bitterlings Rhodeus ocellatus kurumeus and Tanakia limbata (Pisces, Cyprinidae) Reveals Significant Cytogenetic Differences in Morphologically Similar Karyotypes - L. Sola; E. Gornung; H. Naoi; R. Gunji; C. Sato; K. Kawamura; R. Arai; T. Ueda (Genetica, 2003)

Development and disintegration of phragmoplasts in living cultured cells of a GFP?TUA6 transgenic Arabidopsis thaliana plant - K. Ueda; S. Sakaguchi; F. Kumagai; S. Hasezawa; H. Quader; U. Kristen (Protoplasma, 2003)

Changes in neurosteroid biosynthesis during sexual maturation of lacustrine sockeye salmon - S. Matsumoto; H. Yamada; M. Iwata; S. Adachi; K. Yamauchi; H. Ueda (Fish Physiology and Biochemistry, 2003)

Amino acids in stream water are essential for salmon homing migration - T. Shoji; Y. Yamamoto; D. Nishikawa; K. Kurihara; H. Ueda (Fish Physiology and Biochemistry, 2003)

General Utility of the Chicken βB1-Crystallin Promoter to Drive Protein Expression in Lens Fiber Cells of Transgenic Mice - Jennifer R. Taube; Chun Y. Gao; Yoji Ueda; Peggy S. Zelenka; Larry L. David; Melinda K. Duncan (Transgenic Research, 2002)

Chloroplast DNA phylogeography of Fagus crenata (Fagaceae) in Japan - N. Fujii; N. Tomaru; K. Okuyama; T. Koike; T. Mikami; K. Ueda (Plant Systematics and Evolution, 2002)

Renal damage and salt-dependent hypertension in aged transgenic mice overexpressing endothelin-1 - T. Shindo; H. Kurihara; K. Maemura; Y. Kurihara; O. Ueda; H. Suzuki; T. Kuwaki; K.-H. Ju; Y. Wang; A. Ebihara; H. Nishimatsu; N. Moriyama; et al. (Journal of Molecular Medicine, 2002)

Metabolism of 2-Nitrofluorene, an Environmental Pollutant, and 2-Acetylaminofluorene in Fish - O. Ueda; S. Kitamura; Y. Huruse; T. Saito; Y. Kanzaki; Y. Yano; K. Tatsumi; S. Ohta (Bulletin of Environmental Contamination and Toxicology, 2001)

Investigation of physicochemical form of uranium in sediment of brackish Lake Obuchi using sequential extraction procedure - S. Ueda; H. Hasegawa; T. Iyogi; H. Kawabata; K. Kondo (Limnology, 2000)

Nephrotoxicity of D -propargylglycine in mice - R. Konno; M. Ikeda; K. Yamaguchi; Y. Ueda; A. Niwa (Archives of Toxicology, 2000)

Simplified song in an island population of the bush warbler Cettia diphone - S. Hamao; K. Ueda (Journal of Ethology, 2000)

Characteristics of fluctuations in salinity and water quality in brackish Lake Obuchi - S. Ueda; H. Kawabata; H. Hasegawa; K. Kondo (Limnology, 2000)

Polychlorinated Dibenzo- p -Dioxins (PCDDs), Dibenzofurans (PCDFs), Biphenyls (PCBs), and Organochlorine Pesticides in Yellow-Blotched Map Turtle from the Pascagoula River Basin, Mississippi, USA - K. Kannan; M. Ueda; J. A. Shelby; M. T. Mendonca; M. Kawano; M. Matsuda; T. Wakimoto; J. P. Giesy (Archives of Environmental Contamination and Toxicology, 2000)

Rearrangement of cortical microtubules from transverse to oblique or longitudinal in living cells of transgenicArabidopsis thaliana - K. Ueda; T. Matsuyama (Protoplasma, 2000)

Human cytotoxic T-lymphocyte responses specific for peptides of the wild-type Wilms' tumor gene ( WT1 ) product - Y. Oka; O. A. Elisseeva; A. Tsuboi; H. Ogawa; H. Tamaki; H. Li; Y. Oji; E. H. Kim; T. Soma; M. Asada; K. Ueda; E. Maruya; et al. (Immunogenetics, 2000)

Analysis of 5′-upstream non-coding region of FI-carboxymethyl cellulase gene from Aspergillus aculeatus - T. Ooi; K. Morotomi; S. Kinoshita; J. Honda; S. Ueda; M. Arai (Biotechnology Letters, 1999)

Geographical variations in the trophic structure of the plankton community along a eutrophic–mesotrophic–oligotrophic transect - S. Uye; N. Iwamoto; T. Ueda; H. Tamaki; K. Nakahira (Fisheries Oceanography, 1999)
The geographical variations in trophic structure of the plankton community, as defined by total and relative carbon biomass of phytoplankton (PP), bacteria (BA), heterotrophic nanoflagellates (HNF), microzooplankton (MZ), and herbivorous (HNZ) and carnivorous net‐zooplankton (CNZ), were investigated along an inshore–offshore transect from the innermost part of Osaka Bay to the Pacific Ocean off Kii Channel, Japan, in June 1991. Based on physico‐chemical properties of the water and topographical features, the transect was divided into three trophic areas, i.e. eutrophic, mesotrophic and oligotrophic ones. The average carbon biomass of the total plankton community was highest (438 mg m −3 ) in the inshore eutrophic area, and declined steeply offshore (141 and 26.6 mg m −3 in the mesotrophic and oligotrophic areas, respectively). In the offshore oligotrophic area, the relative biomass of BA to PP and the relative biomass of small heterotrophs (i.e. BA, HNF and MZ) to the total heterotrophs were higher than in the other areas, indicating that the microbial food chain predominated. In the mesotrophic area, the biomass of HNZ (primarily copepods) was conspicuously high, even higher than that of PP, suggesting that the traditional grazing food chain prevailed. Because of this short food chain, a productive fishing ground is formed there. In the eutrophic area, the biomass of HNZ was much smaller relative to the enormous biomass of PP, indicating that a considerable amount of primary production was not utilized directly by the metazoan zooplankton. However, the relative contribution of the small heterotrophs to the total heterotrophs’ biomass was higher in this area, as in the oligotrophic area.

Detailed Distribution of Accelerating Foreshocks before a M 5.1 Earthquake in Japan - K. Yamaoka; T. Ooida; Y. Ueda (Pure and Applied Geophysics, 1999)

Spermatozoa in triploids of the rosy bitterling Rhodeus ocellatus ocellatus - K. Kawamura; T. Ueda; K. Aoki; K. Hosoya (Journal of Fish Biology, 1999)
Artificially induced triploid male Rhodeus ocellatus ocellatus showed typical nuptial colorations, irrespective of spermiation. In milt from triploids, abnormal spermatozoa (malformation of the head and mitochondrion, excessive formation of the head, mitochondrion and flagellum, and no flagellum) occurred at 78°4% frequency. Spermatozoa with multiflagella were most common, often with a saccate‐like organ. Many triploid spermatozoa moved actively as long as those of diploids (10·92±0·91 min=mean±S.D., P >0·05), but did not advance like diploids, spinning around until movement ceased. The sperm density in triploids was P P =0·002). In the fertilization test using the eggs of diploids ( n =1500, 30 trials), only one egg developed. The embryo chromosome number was 60 (2·5 n) and the ploidy of spermatozoa contributing to fertilization appears to be 1·5 n. The extremely low fertility of triploid R. o. ocellatus spermatozoa seems to be caused by the reduced motility and large head size of spermatozoa, and the low sperm density of the milt. The ploidy of spermatozoa that are successful in fertilization is likely to be related to the distribution pattern in the DNA content of cells.

Visualization of microtubules in living cells of transgenicArabidopsis thaliana - K. Ueda; T. Matsuyama; T. Hashimoto (Protoplasma, 1999)

Slight difference in primary amino acid sequence of p17 matrix protein of HIV-1 exerts profound influence on its antigenicity - K. Taniguchi; H. Tsuchie; S. Kageyama; M. Iwasaki; T. Takagi; F. Sasao; S. Ueda; T. Kurimura (Archives of Virology, 1998)

Protein kinase C-independent correlation between P-glycoprotein expression and volume sensitivity of Cl− channel - A. Miwa; K. Ueda; Y. Okada (The Journal of Membrane Biology, 1997)

Genomic organization and chromosomal localization of the human casein gene family - Y. Fujiwara; M. Miwa; M. Nogami; K. Okumura; T. Nobori; T. Suzuki; M. Ueda (Human Genetics, 1997)

The upstream region of the isocitrate lyase gene (UPR-ICL) of Candida tropicalis induces gene expression in both Saccharomyces cerevisiae and Escherichia coli by acetate via two distinct promoters - Haruyuki Atomi; K. Umemura; Takanori Higashijima; Tamotsu Kanai; Yoshihisa Yotsumoto; Yutaka Teranishi; Mitsuyoshi Ueda; A. Tanaka (Archives of Microbiology, 1995)

Provocation of respiratory allergy in guinea pigs following inhalation of free toluene diisocyanate - K. Aoyama; J. Huang; A. Ueda; T. Matsushita (Archives of Environmental Contamination and Toxicology, 1994)

Rapid detection of African horsesickness virus by the reverse transcriptase polymerase chain reaction (RT-PCR) using the amplimer for segment 3 (VP3 gene) - K. Sakamoto; R. Punyahotra; N. Mizukoshi; S. Ueda; H. Imagawa; T. Sugiura; M. Kamada; A. Fukusho (Archives of Virology, 1994)

Typing of recent infectious bronchitis virus isolates causing nephritis in chicken - Z. Lin; A. Kato; Y. Kudou; K. Umeda; S. Ueda (Archives of Virology, 1991)

Generation and characterization of the human immunodeficiency virus type 1 mutants - A. Adachi; N. Ono; H. Sakai; K. Ogawa; R. Shibata; T. Kiyomasu; H. Masuike; S. Ueda (Archives of Virology, 1991)

Characterization of a temperature-sensitive mutant in the RNA polymerase PB2 subunit gene of influenza A/WSN/33 virus - K. Yamanaka; N. Ogasawara; M. Ueda; H. Yoshikawa; A. Ishihama; K. Nagata (Archives of Virology, 1990)

Cross-reactivity among cowpox, ectromelia and vaccinia viruses with monoclonal antibodies recognizing distinct antigenic determinants in A-type inclusion bodies - N. Kitamoto; S. Tanimoto; K. Hiroi; H. Miyamoto; N. Wakamiya; S. Ueda; S. Kato (Archives of Virology, 1986)

Polypeptide analysis with monoclonal antibodies of A type inclusion bodies induced by cowpox virus - N. Kitamoto; S. Tanimoto; K. Hiroi; T. Tanaka; H. Miyamoto; N. Wakamiya; K. Ikuta; S. Ueda; S. Kato (Archives of Virology, 1986)

Genetic variants of protease inhibitors against fungal protease and ?-chymotrypsin from hemolymph of the silkworm, Bombyx mori - M. Eguchi; K. Ueda; M. Yamashita (Biochemical Genetics, 1984)

Studies on the serological cross-reaction between Marek's disease virus and herpesvirus of turkeys using monoclonal antibodies to major virus-specific polypeptides - K. Ikuta; K. Nakajima; S. Ueda; S. Kato; K. Hirai (Archives of Virology, 1984)

Cross-reactivity between cowpox and vaccinia viruses with monoclonal antibodies - N. Kitamoto; E. Goto; S. Tanimoto; T. Tanaka; H. Miyamoto; N. Wakamiya; K. Ikuta; S. Ueda; S. Kato (Archives of Virology, 1984)